Analisis Sektor Ekonomi Serta Pengaruh Investasi terhadap Sektor Basis Dan Non Basis 2 Kabupaten Di Provinsi Jawa Tengah - Margaretha Dwi Suprapti Setyaningrum; Niniek Imaningsih; Riko Setya Wijaya (Universitas Batanghari Jambi, 2021)
The purpose of this study was to determine the existence of basic and non-basic sectors, economic sector growth, regional types when viewed from economic growth, as well as how investment affects the basic and non-basic sectors in Cilacap Regency and Sukoharjo Regency in Central Java Province. This study uses time series data with a period of 4 years, namely the period 2016-2019. The analysis technique used is LQ (Location Quetient) analysis, Shift-Share, Klassen typology, simple linear regression analysis using spss 13.0. Based on the results of the LQ analysis, it was revealed that Sukoharjo Regency is a district that is superior to that of Cilacap Regency in terms of the number of its leading sectors. The growth of the economic sectors of the two districts has increased and decreased every year. Based on the results of the regression analysis, it shows that investment has a significant effect on the growth of the basic and non-basic sectors in the two districts.